Employer branding: exploring attractiveness dimensions in a multicultural context - Eger, Ludvík; Mičík, Michal; Gangur, Mikuláš; Řehoř, Petr (Technological and Economic Development of Economy, 2019)
Attracting and retaining talented employees and gaining competitive advantage are important for organizations around the world. This study identifies and operationalizes the components of employer attractiveness from the perspective of potential employees. The study tests the employer attractiveness scale (EmpAt) by identifying the attractiveness dimensions of an employer brand among business students in the Czech Republic through exploratory factor analysis. We also search for similarities and differences among employer attractiveness dimensions through a cross-cultural comparison based on the results of previous studies. Businesses in today’s globalised world need to attract potential employees globally and determine whether it would be better to use one corporate strategy or to customize their employer brand according to the cultural differences between countries. National, cultural, and gender differences are also investigated. The findings show factors that business students give the highest importance to when searching for an employer and that the factor’s importance is influenced by gender. The findings of this study can be used to track the perceptions of current job applicants about the company and to appeal to “suitable target audiences” – potential employees. The results can be used by HR experts and practitioners in formulating and executing their communication and recruitment strategies. First published online 10 April 2019